2005
DOI: 10.1354/vp.42-4-489
|View full text |Cite
|
Sign up to set email alerts
|

Hemangiomatosis Associated with Osteolysis of the Mandible in a Dog Resembling Gorham-Stout Disease in Humans

Abstract: Abstract.A 6-month-old female German Shepherd Dog died as a result of profuse oral bleeding. At postmortem examination, the oral cavity showed visible roots of the right mandibular fourth premolar and first molar teeth and, in addition, they were very mobile and compressible. Radiographs showed a generalized radiolucency in the body of the right mandible, with evidence of resorption of the affected alveolar bone. Histologically, the lesion of the right mandible was characterized by the lysis of bony structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The pathology in these dogs was compared to Winchester syndrome in humans, because lysis was multicentric, bone was replaced by fibrous rather than vascular tissue, and three of the four dogs were related (lineage of the fourth dog was unknown). A second case report described an immature German shepherd dog that died as a result of profuse oral bleeding (8). In this dog, the clinical, radiographical, and histological presentation was similar to Gorham's disease, although the primary differential diagnosis of primary haemangioma could not be ruled out.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The pathology in these dogs was compared to Winchester syndrome in humans, because lysis was multicentric, bone was replaced by fibrous rather than vascular tissue, and three of the four dogs were related (lineage of the fourth dog was unknown). A second case report described an immature German shepherd dog that died as a result of profuse oral bleeding (8). In this dog, the clinical, radiographical, and histological presentation was similar to Gorham's disease, although the primary differential diagnosis of primary haemangioma could not be ruled out.…”
Section: Discussionmentioning
confidence: 98%
“…We describe the clinical, radiological and histopathological features, and discuss similarities with the human condition known as Gorham's disease. Although two previous reports of canine idiopathic osteolysis have been published, to the authors' knowledge, this is the first case report documenting the natural progression of idiopathic primary osteolysis in a dog (7,8).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Accordingly, the term angiomatosis has been used ambivalently in literature to describe both, neoplastic, as well as malformative, proliferative vascular lesions (11)(12)(13). Cases of mandibular angiomatosis have been reported in young animals before, including a 2-month-old Holstein calf and a 6-month-old dog from Canada and Spain, respectively (14,15). Similar lesions have been observed in the orbit, the meninges, ovaries, intestine, and skin of horses but, to the authors' knowledge, have never been observed within the mandible (11)(12)(13)16).…”
Section: Introductionmentioning
confidence: 99%